Les aspects productifs de l’économie informelle. Recherche des indicateurs pour une réponse au développement en Afrique - Muheme, Bagalwa Basemake Gaspard (Afrika Focus, 1992)
This article aims at deepening our understanding of the concept informal economy. It is the case that definitions with regard to the reality of this phenomenon vary in function of the author and the countries studied. Indeed, the concept needs to be discussed right across the countries of the West, the East European countries under the old system, i.e. until 1990, and the countries of Africa. With regard to the informal economy in Africa, the characteristics of irrationality and the lack of initiative on the part of economic agents has often been posited. However, this economic phenomenon is neither exclusive to Africa nor is it confined to the present time. Only a comparative approach will enable one to arrive at some precision with regard to the concepts used in the economic literature. Our primary goal is to place this informal economy within the global perspective of African development. This informal economy sets itself up as a creative attempt, often able to give efficient answers, whether in the field of agriculture or in other forms of activity, to the challenges of badly mismanaged societies. KEY WORDS: informal economy, plural activities, integrative economy, petty commodity production and consumption, interdependency of sectors